Phishing and advanced persistent threats - Brandao, Pedro Ramos (2022)
The paper addresses one of the techniques mor used by Advanced Persistent Threats attacks, phishing. The paper demonstrates the complexity of the technique, explains how attacks can be carried out, and presents defense techniques, and strategies against phishing attacks. The article also presents a summary description of what an Advanced Persistent Threat attack is. This description characterizes this type of attack.